PERAN BUMDES WIJAYA KUSUMA DALAM PROGRAM PEMBAYARAN PAJAK KENDARAAN BERMOTOR UNTUK PENINGKATAN PAD KABUPATEN TABANAN - Devi, I Gusti Agung Ayu Shintia; Winaya, I Ketut; Supriliyani, Ni Wayan (CITIZEN CHARTER; Vol 2 No 1 (2022): Administrasi Publik 2022, 2022)
BUMDES is a business institution that is managed independently by the community and village government in an effort to strengthen the village economy. The purpose of this study is to determine the role of Village-Owned Enterprises in increasing local revenue through motor vehicle tax payments. This research uses a qualitative descriptive research type. Determination of informants using snowball sampling technique. The role of BUMDES is grouped based on the theory of Henry Mintzberg, namely interpersonal relationships, relationships between information, and decision makers. This study found that the role of BUMDES Wijaya Kusuma in the motor vehicle tax payment program to increase the local revenue of Tabanan Regency was able to help increase the regional original income of Tabanan Regency optimally. This is indicated by an increase in the local revenue of Tabanan district before and after the existence of the BUMDES, but the dissemination of information must be improved. Keywords: The Role of BUMDES, Tabanan Regency, Regional Original Income, Payment of Motor Vehicle Taxes